Makna Teologis Pembangunan Bendungan Tapin di Desa Pipitak Jaya, kabupaten Tapin, Kalimantan Selatan - May Linda Sari; Imistiana; Iemelda Marya Anggreaini (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2023)
This article is a report of research along August to December 2022 on development effects to local community especially villagers around the dam construction of Tapin, in Tapin district, South Kalimantan province. The dam construction itself was spend a huge funds, needed almost 20 years on construction process since process of planning, consultation, program outreach to the community around the construction, land acquisition and finishing. The dam will totally drown 2 village and it will change aspects in community. The research is using kualitative descriptive method of Auguste Comte on Law of the three Stages and there are three result research i.e. Firstly, the communities around the dam construction were accepted the construction; Secondly, the dam construction actually has impact in developt of ecological and spiritual value on water. And thirdly, the dam contruction has positive impact in communities, ecologically and economically.